Roles of MicroRNAs in Glucose and Lipid Metabolism in the Heart - Du, Hengzhi; Zhao, Yanru; Li, Huaping; Wang, Dao Wen; Chen, Chen (Frontiers in Cardiovascular Medicine, 2021)
MicroRNAs (miRNAs) are small non-coding RNAs that participate in heart development and pathological processes mainly by silencing gene expression. Overwhelming evidence has suggested that miRNAs were involved in various cardiovascular pathological processes, including arrhythmias, ischemia-reperfusion injuries, dysregulation of angiogenesis, mitochondrial abnormalities, fibrosis, and maladaptive remodeling. Various miRNAs could regulate myocardial contractility, vascular proliferation, and mitochondrial function. Meanwhile, it was reported that miRNAs could manipulate nutrition metabolism, especially glucose and lipid metabolism, by regulating insulin signaling pathways, energy substrate transport/metabolism. Recently, increasing studies suggested that the abnormal glucose and lipid metabolism were closely associated with a broad spectrum of cardiovascular diseases (CVDs). Therefore, maintaining glucose and lipid metabolism homeostasis in the heart might be beneficial to CVDs patients. In this review, we summarized the present knowledge of the functions of miRNAs in regulating cardiac glucose and lipid metabolism, as well as highlighted the miRNA-based therapies targeting cardiac glucose and lipid metabolism.